PARIPEDAS: A Smart Rural Tourism Model Using SEM Analysis Through The Coastal Village Community Empowerment - Riwayani; Ira Pane; Ardi; Mansur Tanjung; Shofian Nanda Adiprayoga; Tirta Anugerah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Tourists turn to rural tourism because of its distinctiveness in relation to nature, the hospitality of the locals, and its unique food. However, Central Tapanuli Regency's tourism growth remains uneven due to a lack of infrastructure, knowledge, and policies that prioritize urban regions. The Central Tapanuli Regency Government has to create a tourist strategy that takes coastal rural development into account. In Central Tapanuli Regency, the Smart Rural Tourism Model (PARIPEDAS) encourages the growth of tourism by utilizing village potential, community engagement, natural preservation, and local knowledge. The study employs a mixed methodological approach to ascertain policymakers' perspectives, assess the function of rural communities, and develop a PARIPEDAS model using Structural Equation Modeling (SEM) analysis based on Central Tapanuli Regency's coastline potential. While the PARIPEDAS model requires more research to be in line with regional development plans, the research determined that the ideal approach was to empower and include coastal communities in the implementation of tourism and development, concentrating on the distinctive value of tourist attractions and protection of natural assets.